2021
DOI: 10.17485/ijst/v14i17.235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Radiation on Temperature and Concentration on MHD Free Convection Flow Past a Vertical Porous Plate in the Presence of Chemical Reaction and Heat Source Parameter

Abstract: Objective: To study the effects of chemical reaction and heat source parameter on MHD Free Convection Flow Past a Vertical Porous Plate. Method: The problem is represented by coupled non-direct fractional differential conditions. The non-dimensional conditions of the issue have been tackled mathematically utilizing the Finite-Element strategy. Findings: The effects of governing parameters such as chemical reaction, heat source, permeability, radiation and many others are discussed quantitatively with the help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Padmaja and Kumar 27 gave the analysis of heat and mass transfer of MHD nanofluid, along with radiative heat flux. Lakshmi et al 28 presented consequences of chemical, heat distribution factors on MHD Convection movement through a penetrable sheet. Seth et al 29 considered, impact of Hall current and rotation on unsteady MHD in a porous form of media with thermal and mass dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Padmaja and Kumar 27 gave the analysis of heat and mass transfer of MHD nanofluid, along with radiative heat flux. Lakshmi et al 28 presented consequences of chemical, heat distribution factors on MHD Convection movement through a penetrable sheet. Seth et al 29 considered, impact of Hall current and rotation on unsteady MHD in a porous form of media with thermal and mass dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…7 Sankar Reddy et al 8 reported an unstable MHD convective heat and mass transfer flow of micropolar fluid across a semi-infinite vertical moving porous plate in the presence of radiation. The impacts of the chemical reaction and heat source parameters on MHD Free Convection Flow Past a Vertical Porous Plate were investigated by Lakshmi et al 9 Reddy et al 10 investigate the effects of radiation and chemical reactions on unsteady transient MHD free convective and heat transfer of a viscous, electrically insulating fluid across an unexpectedly initiated infinite vertical porous plate while taking into account viscous dissipation. The finite element approach for unstable MHD temperature and mass transmission presented by Kishan et al 11 enabled the normal flow of polar fluids over a vertically moving permeable plate in a porous medium with convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Sankar Reddy et al 8 reported an unstable MHD convective heat and mass transfer flow of micropolar fluid across a semi‐infinite vertical moving porous plate in the presence of radiation. The impacts of the chemical reaction and heat source parameters on MHD Free Convection Flow Past a Vertical Porous Plate were investigated by Lakshmi et al 9 …”
Section: Introductionmentioning
confidence: 99%
“…Thumma et al 31 discussed nonlinear thermal radiation effect on Eyring–Powell nanofluid flow across a nonlinear elongating sheet with Joule and viscous dissipation. Appidi et al 32 studied the effects of chemical reaction and heat source parameter on MHD free convection flow past a vertical porous plate. Appidi et al 33 studied the influence of Soret and Dufour numbers on an unsteady MHD free convection of flow of heat and mass transfer through porous media.…”
Section: Introductionmentioning
confidence: 99%